Investigations into variations in local cationic environment in layered oxide series InGaO3(ZnO)(m) (m=1-4) - Narendranath, Soumya B.; Yadav, Ashok Kumar; Ajithkumar, Thalasseril G.; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Dey, Krishna K.; Raja, Thirumalaiswamy; Devi, R. Nandini (Dalton Transactions, 2014)
Layered oxides of the series InGaO3(ZnO)(m) (m = 1-4) are interesting due to their structural anisotropy. Here, we report a comprehensive study of their structural details, focusing on the local cationic environment in bulk powder samples by MASNMR and EXAFS, which is hitherto not attempted. It is found that the Ga geometry varies gradually from pure pentacoordinated to a mixture of penta and tetracoordinated with increasing amounts of tetracoordination as we move across the series, contrary to previous reports suggesting exclusively trigonal bipyramidal coordination in all the compounds. A similar observation is also made in the case of Zn and structural evolution involving the dissolution of Ga in a ZnO4 tetrahedral network in a sandwich layer can be discerned, as the insulating ZnO layer size increases.